2015
DOI: 10.1103/physrevb.92.245411
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium phonon mean free paths in anharmonic chains

Abstract: Harnessing the power of low-dimensional materials in thermal applications calls for a solid understanding of the anomalous thermal properties of such systems. We analyze thermal conduction in one-dimensional systems by determining the frequency-dependent phonon mean free paths (MFPs) for an anharmonic chain, delivering insight into the diverging thermal conductivity observed in computer simulations. In our approach, the MFPs are extracted from the length dependence of the spectral heat current obtained from no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 44 publications
(85 reference statements)
7
48
0
Order By: Relevance
“…The nonequilibrium heat current can be further decomposed for different frequencies, as recently demonstrated by Sääskilahti et al [31,32]. Here, we extend their method to include the in-out decomposition.…”
Section: Spectral Decompositionmentioning
confidence: 97%
See 4 more Smart Citations
“…The nonequilibrium heat current can be further decomposed for different frequencies, as recently demonstrated by Sääskilahti et al [31,32]. Here, we extend their method to include the in-out decomposition.…”
Section: Spectral Decompositionmentioning
confidence: 97%
“…First, the system can either have fixed [32,[42][43][44] or periodic boundary conditions [9,23,24,36,39] along the transport direction. Second, the nonequilibrium heat current can be generated by different methods, including the velocity rescaling method by Jund and Jullien [24], the velocity-swapping method by Müller-Plathe [23], or the thermostat method [6,32,[42][43][44]. It has been found that the results do not sensitively depend on the methods chosen (see, e.g., [9]).…”
Section: B Nonequilibrium Molecular Dynamics Methodsmentioning
confidence: 99%
See 3 more Smart Citations